THE DETERMINATION OF SHARIA GOVERNANCE ON BAITUL MAAL WA TAMWIL (BMT) IN DEPOK CITY - Sepky Mardian; Izzatun Nissa; Nursanita Nasution (Universitas Airlangga, 2019)
This study aimed to examine the influence of organizational culture, organizational commitment and internal control over sharia governance. The object in this study was BMT in Depok City, West Java. Sampling was done by purposive sampling technique to obtain a sample of 5 BMTs. While respondent sampling was done by simple random sampling technique. Data collection techniques in the study were conducted by questionnaire. The type of research was associative by using methods of Partial Least Square (PLS). The study found that organizational culture and internal control have a significant positive influence on sharia governance. While organizational commitment has a positive but not significant effect on sharia governance.